The Influence of Digital Training, Digital Literacy and The Work Environment on Teachers Digital Competencies Which Impact Teacher Performance in the Era of Education Digitalization - Cecylia, Cecylia; Rudianto, Rudianto; Rante, Jones Zenas; Pakpahan, Marisi; Marsella, Prasastiara Eka (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
In the era of educational digitalization, teachers' digital competence is very important to improve the quality of learning. This study aims to analyze the influence of digital training, digital literacy, and work environment on teachers' digital competence which has an impact on teacher performance in SMA and SMK Cahaya Sakti, East Jakarta. The research method used was quantitative with a path analysis approach and involved 44 respondents who were teachers at the institution. The results showed that digital training did not have a significant influence on teachers' digital competence, with a T-statistical value of 1.395 and a P-value of 0.082. On the other hand, digital literacy was proven to have a significant influence on digital competence (T-statistic 3.114, P-value 0.001) and the work environment also had a significant effect (T-statistic 1.926, P-value 0.027). Teachers' digital competence has a positive and significant effect on teacher performance (T-statistic 3.264, P-value 0.001). However, digital literacy and the work environment did not show a significant influence on teacher performance. Based on these findings, it is recommended that Cahaya Sakti High School and Vocational School improve digital training programs that are more focused and applicative, as well as integrate digital literacy in the teacher development curriculum. Additionally, it is important to create a work environment that supports educational technology innovation. With these measures, it is hoped that teachers' digital competence can be improved, which in turn will have a positive impact on their performance in the learning process. Further research is also needed to explore other factors that can affect digital competence and teacher performance